Studi Kelayakan Kebun Raya sebagai Sumber Belajar Lingkungan Melalui Tinjauan Infrastruktur dan Aksesibilitas - Ratri Harianti Putri; Maddatuang Maddatuang; Abdul Malik; Hasriyanti Hasriyanti; Ramli Umar (Jurnal Penelitian Pendidikan Geografi, 2025)
Indonesia’s status as a tropical country makes it rich in biodiversity, so that botanical gardens in addition to being used as tourist attractions, also function in the field of education. This study aims to determine and analyze the physical condition and eligibiltion of the Massenrempulu Botanical Garden as a source of environmental learning and to determine and analyze the feasibility of the Massenrempulu Botanical Garden as a source of environmental learning. The research method used is the mixed method. The data analysis technique uses a Likert scale and SWOT qualitative analysis. The results of the study show that, the physical condition of the Massenrempulu Botanical Garden contains several infrastructures, namely: gates, management offices, mosques and toilets, hotmix roads and boulevards, gicok roads, concrete roads, reservoirs, and gazebos. Environmental elements have an average percentage of 78.38%, infrastructure or facilities of 71%, accessibility/affordability of 82.67%. The three percentages of these indicators are 77.38%, meaning that the Massenrempulu Botanical Garden is included in the category of being feasible as a source of environmental learning.. The Botanical Garden has great potential as a tourist and educational destination, but is hampered by several weaknesses such as lack of maintenance and funding. Therefore, it is necessary to implement strategies to improve the quality and attractiveness of the Botanical Gardens, such as improving maintenance and provision, and developing information system technology.